Theorizing Twilight critical essays on what's at stake in a post-vampire world - Parke, Maggie; Wilson, Natalie, 1971- (McFarland & Company, Inc., Publishers, 2011)
"Since the publication of Twilight in 2005, Stephenie Meyer's four-book saga has become a world-wide sensation, inciting screams of delight from loyal fans, sighs of derision from detractors, and fervent pronouncements about what "Team" one is on. These accessible essays examine the texts, the films, and the fandom, exploring the series' cultural reach and impact"--Provided by publisher.